2018
DOI: 10.1016/j.bjorl.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional effects of voice therapy in patients affected by unilateral vocal fold paralysis due to cancer

Abstract: Vocal rehabilitation improves perceptual and acoustic voice parameters and voice handicap index, besides favor glottal closure in patients with unilateral vocal fold paralysis. The results were also permanent during the period of 1 year. The Jitter value, when elevated, is a risk factor for the voice therapy success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
2
2
0
1
Order By: Relevance
“…Following voice therapy, the shimmer parameter decreased, but there were no statistically significant differences. Barcelos et al [12] reported similar results as our study. They emphasized the importance of jitter parameter as a predictive factor for the success of voice therapy, providing guidelines to clinicians as a foundation for further research.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Following voice therapy, the shimmer parameter decreased, but there were no statistically significant differences. Barcelos et al [12] reported similar results as our study. They emphasized the importance of jitter parameter as a predictive factor for the success of voice therapy, providing guidelines to clinicians as a foundation for further research.…”
Section: Discussionsupporting
confidence: 92%
“…There was no recovery of the vocal folds in terms of mobility and no clear evidence that there was an improvement in the muscle tone of the paralyzed vocal fold, but the compensatory movement of the healthy vocal fold en- [12,[30][31][32]. These findings are in accordance with the results of other authors who discuss the recovery of innervation in 9-12 months [19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results showed significant improvement in the VHI-30 through time that persisted after cessation of VT (Figure 1 ), irrespective of vocal fold position and glottal competence. These findings may translate the effect of time and personal adaptation on functional recovery after VT [ 12 , 23 ]. Other studies that included a UVFP group not submitted to VT or any other intervention also showed improvement in phonation and videoendoscopic reductions in glottal gap size with time [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos (10)(11)(12) relatam a importância da análise multidimensional da voz, compreendida por um conjunto de métodos que se complementam. As análises podem ser de cunho subjetivo e/ou objetivo, dependendo da necessidade do avaliador.…”
Section: Introductionunclassified